The Impact of Digital Case-Based Learning on Higher-Order Thinking Skills of Civil Engineering Students - Santosa, Tomi Apra (eScience Humanity Journal, 2025)
The rapid advancement of digital technology in higher education has transformed traditional teaching methods into more interactive and learner-centered approaches. This study investigates the impact of Digital Case-Based Learning (D-CBL) on the development of Higher-Order Thinking Skills (HOTS) among civil engineering students. A quasi-experimental design with a pretest-posttest control group was employed, involving 96 undergraduate civil engineering students enrolled in a Structural Analysis course. The experimental group received instruction through CBL supported by a digital learning platform that integrated interactive case scenarios, multimedia resources, and collaborative discussion forums, while the control group was taught using conventional lecture-based methods. Data were collected using a validated HOTS assessment instrument focusing on the dimensions of critical thinking, problem-solving, analytical reasoning, and decision-making. Statistical analyses, including paired sample t-tests and ANCOVA, were conducted to evaluate differences in learning outcomes between the two groups. The findings revealed that students exposed to D-CBL demonstrated a significant improvement in HOTS (p < 0.05) compared to those taught through traditional methods. The integration of authentic civil engineering case studies with digital tools fostered deeper conceptual understanding, enhanced collaborative problem-solving, and stimulated independent learning.